Groehnaltica batophiloides, a new genus and species of flea-beetles (Coleoptera: Chrysomelidae) from Baltic amber, described using X-ray microtomography - Bukejs, Andris; Reid, Chris A. M.; Biondi, Maurizio (Zootaxa, 2020)
Based on a well-preserved specimen from Eocene Baltic amber, Groehnaltica batophiloides gen. nov. and sp. nov. (Coleoptera: Chrysomelidae: Galerucinae: Alticini) is described and illustrated using X-ray micro-computed tomography (μCT). The new monotypic genus is compared with fossil and extant flea-beetle genera. In the extant Eurasian fauna Groehnaltica shows most similarity to Batophila Foudras, 1859. However, it is also similiar to a Palaeotropical group of genera, including Bikasha Maulik, 1931, and Lanka Maulik, 1926. Groehnaltica batophiloides is the tenth member of Alticini to be described from Baltic amber, adding to our understanding of the evolutionary history of this diverse group of beetles.